Mutations in Two Aphid-Regulated β-1,3-Glucanase Genes by CRISPR/Cas9 Do Not Increase Barley Resistance to Rhopalosiphum padi L - Kim, Sung-Yong; Bengtsson, Therese; Olsson, Niklas; Hot, Vehbo; Zhu, Li-Hua; Åhman, Inger (Frontiers in Plant Science, 2020)
Callose deposition is induced in plants by various stress factors such as when plants are attacked by herbivores and pathogens. In the case of aphids, callose plugging of aphid-damaged phloem sieve tubes is expected to reduce aphid access to the phloem sap, while aphid-induced upregulation of callose-degrading β-1,3-glucanase genes in the host plant might counteract this negative effect on aphid performance. We have tested this hypothesis with barley mutants in which one or both of two β-1,3-glucanase genes (1636 and 1639) have been mutated by CRISPR/Cas9 technique in cv. Golden Promise. These two genes were previously found to be upregulated by the cereal pest Rhopalosiphum padi L. in susceptible barley genotypes. Four 1636/1639 double mutant, three 1636 single mutant and two 1639 single mutant lines were tested for aphid resistance along with control lines. All mutant lines had single base insertions, causing frame shifts and premature stop codons. Three of the four double mutant lines showed significantly reduced β-1,3-glucanase activity, and bacterial flagellin-induction resulted in significantly more callose formation in the leaves of double mutant compared to control and single mutant lines. However, we found no effect of these modified plant traits on barley resistance to R. padi. Both genes were confirmed to be upregulated by R. padi in Golden Promise. The gene 1637 is another β-1,3-glucanase gene known to be upregulated by R. padi in barley and was here found to be higher expressed in a double mutant line when compared with a control line. If this can compensate for the general reduction of β-1,3-glucanase activity in the double mutants is difficult to discern since phloem concentrations of these proteins are unknown.